Bilirubin-microbiota interaction: molecular mechanisms and therapeutic strategies in neonatal jaundice - Yan, Wenlong; Du, Ning; Zhang, Kun; Yang, Pingping; Guo, Jing; Xu, Lingfen (Frontiers in Microbiology, 2026)
Recent studies have revealed a complex interplay between bilirubin metabolism and the gut microbiota. Bilirubin functions as a potent antioxidant and signaling molecule in humans, and its concentration-dependent effects on distinct microbial taxa indicate that the compound exerts selective pressure on the gut ecosystem. The gut microbiota modulates bilirubin metabolism by altering intestinal pH, producing and activating Bilirubin metabolic enzyme, and bile acids. Because perturbations in bilirubin handling are especially common—and potentially neurotoxic—in neonates, a concise synthesis of recent progress is warranted. Here we review how microbial communities reshape bilirubin flux, how bilirubin and its conjugates, in turn, sculpt microbial ecology, and how the dynamic equilibrium between conjugated and unconjugated bilirubin in hyperbilirubinaemia is influenced by the microbiome. Regulating gut microbiota to accelerate bilirubin clearance or attenuate its toxicity may therefore offer a tractable therapeutic avenue.